A Middle English Witness of Guy de Chauliac’s On Bloodletting. - Esteban-Segura, María Laura (My University, 2023)
The objectives of this paper are the following: first, to investigate the transmission of the text; second, to assess the main codicological and palaeographical features of the treatise; third, to explain the principles followed in the edition of the text, which remains hitherto unedited; and finally, to examine the language of the text in order to locate it geographically. The physical analysis of the codex will be carried out by close, first-hand inspection of the manuscript as well as of its digitised images. The edition of the text will adjust to the semi-diplomatic tenets, which postulate faithfulness to the original witness. As for the linguistic analysis, it will be based on the methodology put forward by the Linguistic Atlas of Late Mediaeval English (LALME) (McInstosh et al. 1986). The appraisal of all the aspects mentioned above will help to yield a complete picture of the treatise and to place it in its material and cultural context.
Keywords: Inglés medieval - Fuentes; Guy de Chauliac - Crítica textual; Manuscritos ingleses - Edición; Medicina medieval - Fuentes; GUL MS Hunter 307; Guy de Chauliac; Middle English; Bloodletting; Medical prose